Production and Optimization of L-asparaginase by Bacillus sp. KK2S4 From Corn Cob - Makky, Essam A.; Jee, Jian Ong; Karim, Md. Rezaul; Lee, Chin Mei (African Journal of Biotechnology, 2013)
L-Asparaginase (L-asparagine amido hydrolase, E.C.3.5.1.1) is an important enzyme which has anti-tumor properties. This paper describes the production and optimization of L-asparaginase by Bacillus sp. KK2S4 utilization of ground corn cob waste as substrate to reduce and manage the waste in our environment. Thirty-nine (39) bacterial isolates were screened for their L-asparaginase productivity and protein content. Only Bacillus sp KK2S4 was identified before and selected as the most potent isolate. Modified M9 (MM9) minimal complete medium (glucose free) was used as production media for enzyme production. The highest enzyme production was detected at pH 5.0 in presence of lactose and NaNO3 as the best carbon and nitrogen sources with high activity increasing percentage of 1058.9, 377.3 and 566.7%, respectively.